Bibliometric Mapping of Public Knowledge on Megathrust Earthquake Disaster Mitigation - Retna Pebrianti; Iip Permana (YASIN, 2026)
Public knowledge of megathrust earthquake mitigation is essential for strengthening disaster preparedness and supporting disaster risk reduction. Although earthquake mitigation research has continued to expand, bibliometric evidence positioning public knowledge within this body of literature remains limited. This study maps the development and thematic structure of research on public knowledge regarding megathrust earthquake disaster mitigation published between 2016 and 2026. A descriptive quantitative approach employing bibliometric analysis was used. Data were retrieved from Google Scholar through Publish or Perish using the keywords disaster mitigation, earthquake preparedness, megathrust earthquake, disaster risk communication, and public knowledge. A total of 998 documents meeting the inclusion criteria were exported in RIS format and analyzed using VOSviewer 1.6.20 through network, overlay, and density visualizations. The findings reveal that the research landscape is dominated by the keywords earthquake, knowledge, tsunami, hazard, and mitigation, which constitute the central nodes of the bibliometric network. The network analysis identified 181 keywords distributed across nine clusters, with 4,768 links and a total link strength of 13,732. Although knowledge emerged as a major thematic node, density visualization showed that disaster communication, general knowledge, and indigenous knowledge remain less extensively investigated than technical disaster-related themes. These findings demonstrate that megathrust earthquake mitigation research continues to prioritize technical and hazard-oriented dimensions, whereas public knowledge and risk communication remain underdeveloped areas of inquiry. This study contributes a systematic overview of the intellectual structure and research gaps within the field and highlights the need for further investigation of public knowledge, indigenous knowledge, and risk communication, particularly in the context of Mentawai–Siberut megathrust earthquake mitigation.